Respuesta :

Answer:

Step-by-step explanation:

F(x) = 7 - 5x + 7x²

f(-9) = 7 - 5*(-9) + 7*(-9)²

       = 7 + 45 + 7*81

      = 7 + 45 + 567

      = 619

Gyzmo

Answer:

f(-9) = 619

Step-by-step explanation:

To solve for f(-9), plug -9 in for x in the equation of f(x). In other words, change all x's into -9 in the equation 7 - 5x + 7x² and then solve.

f(x) = 7 - 5x + 7x²

Plug in -9 for x.

f(-9) = 7 - 5(-9) + 7(-9)²

Simplify. 5(-9) = -45,   7(-9)² = 7(81) = 567

f(-9) = 7 + 45 + 567

Solve.

f(-9) = 619

The answer is 619.

I hope this helps. If you need clarifications of anything, feel free to ask. Happy studying. :)

ACCESS MORE